2010
DOI: 10.13057/biofar/f080202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beluntas (Pluchea indica) leaf extract on mice spermatogenesis

Abstract: Amalina N, Suyatmi, Suparyanti EL. 2010. Effect of beluntas (Pluchea indica) leaf extract on mice spermatogenesis. Biofarmasi 8: 47-51. This research aimed to determine the effect of beluntas (Pluchea indica L.) leaf extract in habiting spermatogenesis. Flavonoids can inhibit aromatase enzyme that function to catalyze the conversion of androgens into estrogen so that the level of the testosterone hormone will increase. The high concentration of testosterone will affect on the feedback to the pituitary, that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Many plants and their constituents have been investigated for their antifertility potential [105]. Interestingly, P. indica has been used orally in men as an antifertility alternative medicine [20,21,106].…”
Section: Antifertility Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many plants and their constituents have been investigated for their antifertility potential [105]. Interestingly, P. indica has been used orally in men as an antifertility alternative medicine [20,21,106].…”
Section: Antifertility Activitymentioning
confidence: 99%
“…Spermiogenesis is the last phase of spermatogenesis in which spermatids are converted to spermatozoa, which play a substantial function in the fertilization process [107]. It was reported that the leaf extract (doses 1.4, 2.8, and 5.6 mg/kg for 10 days) caused a decrease in the number of spermatid cells in male mice when the dose increased [106]. It was found that the treatment of white male adult rats with leaf tannin reduced the number of spermatozoa and spermatids [20,21].…”
Section: Antifertility Activitymentioning
confidence: 99%
“…Pharmacological studies have found that P. indica inhibits spermatogenesis (6), induces apoptosis of nasopharynx cancer cells (7), has anti-inflammatory (8), antipyretic (9), antibacterial (10), antioxidant (11) and antidiabetic activities (12). P. indica produces secondary metabolites such as flavonoids, alkaloids, tannins, and saponins (13).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional medicinal plants with effects on infertility must be acceptable to the community, safe, productive, reversible, and not affect with sexual intercourse. 11, 12 Since natural medications were believed to be healthier than synthetic ones, interest in using medicinal herbs and traditional medicine increased, and it began mostly in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric and other Indonesian medicinal herbs have also been shown to affect male antifertility possibly. [12][13][14][15][16] Curcuma longa and curcumin For thousands of years, natural products have been used in traditional medicine and have proven to be a promising source of components for new drug development. 14,15 Turmeric (Curcuma longa Linn) is cultivated worldwide in subtropical and tropical regions, stems from Indonesia, India, and Southeast Asia and belongs to the Zingiberaceae family.…”
Section: Introductionmentioning
confidence: 99%